212k views
3 votes
Write the rational expression in lowest terms. x^2-9x+8/x^2 + x-3; x^2-9x+8/x^2+2x-3 (Simplify your answer.)

User Jon Ramvi
by
5.6k points

1 Answer

7 votes

Answer:


(x-8)/(x+3)

Explanation:

Given expression,


(x^2-9x+8)/(x^2+2x-3)


=(x^2-(8+1)x+8)/(x^2+(3-1)x-3)


=(x^2-8x-x+8)/(x^2+3x-x-3)


=(x(x-8)-1(x-8))/(x(x+3)-1(x+3))


=((x-1)(x-8))/((x-1)(x+3))


=(x-8)/(x+3)

Since, further simplification is not possible,

Hence, the given rational expression in lowest terms is,


(x-8)/(x+3)

User Adrian Tanase
by
6.3k points